2023
DOI: 10.3389/fpsyt.2023.1306194
|View full text |Cite
|
Sign up to set email alerts
|

Female-specific pharmacotherapy in ADHD: premenstrual adjustment of psychostimulant dosage

M. de Jong,
D. S. M. R. Wynchank,
E. van Andel
et al.

Abstract: ObjectiveAttention-Deficit/Hyperactivity Disorder (ADHD) is a common neurodevelopmental condition which is underdiagnosed and undertreated in women. For decades, the ADHD field has called for more insight into female-specific therapy. Preliminary findings postulate that changes in sex hormones during the menstrual cycle may influence the effectiveness of psychostimulant medication. Yet, pharmacotherapeutic interventions tailored to women with ADHD remain scarce. Previously, our group showed an increase in mood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Recently, we published a case series that demonstrates the potential benefits of increased psychostimulant dosage in the premenstrual phase. We reported relief of worsening ADHD and mood symptoms premenstrually in all nine consecutive cases [42]. But beyond psychopharmacology, multi-modal treatment for (women with) ADHD is optimal to improve treatment outcome [21].…”
Section: Merging Practice and Researchmentioning
confidence: 83%
See 4 more Smart Citations
“…Recently, we published a case series that demonstrates the potential benefits of increased psychostimulant dosage in the premenstrual phase. We reported relief of worsening ADHD and mood symptoms premenstrually in all nine consecutive cases [42]. But beyond psychopharmacology, multi-modal treatment for (women with) ADHD is optimal to improve treatment outcome [21].…”
Section: Merging Practice and Researchmentioning
confidence: 83%
“…Research has shown that the impact of sex hormones on mood and cognitive function is significant in women [18,[29][30][31][32][33][34][35][36][37][38][39]. This may be more pronounced in women with ADHD [40][41][42]. Our group previously showed that women with ADHD have a higher prevalence of mood disorders than what is seen in the general population during three major periods of reproductive hormone fluctuation: the premenstrual period, postpartum, and (peri)menopause [20].…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations